Mutations in ampD cause hyperproduction of AmpC and CmcB β-lactamases and high resistance to β-lactam antibiotics in Chromobacterium violaceum - Luís Gustavo Laranjeiro; Carlos Eduardo M. Neme; Maristela Previato-Mello; Bianca B. Batista; Isabel Henriques; José F. da Silva Neto (Microbiology Spectrum)
ABSTRACT Bacterial resistance to β-lactam antibiotics mediated by β-lactamase enzymes is widespread worldwide. Chromobacterium violaceum, an environmental Gram-negative bacterial pathogen, is intrinsically resistant to some β-lactam antibiotics. In this work, we found that mutations in an ampD gene, encoding a peptidoglycan-recycling amidase, cause hyperproduction of two chromosomal β-lactamases (AmpC and CmcB), conferring high β-lactam resistance in C. violaceum. Susceptibility tests using ΔampC, ΔcmcB, and ΔcmcBΔampC mutant strains revealed specific susceptibility profiles to penicillin, cephalosporin, and carbapenem β-lactams, suggesting that AmpC is a broad-spectrum β-lactamase (penicillinase and cephalosporinase), while CmcB is a narrow-spectrum metallo-carbapenemase. β-galactosidase assays indicate that the expression of ampC and cmcB increased in response to β-lactams. We isolated C. violaceum spontaneous mutants resistant to the antibiotic ceftazidime and found that most mutants were also resistant to several other β-lactams and overexpressed ampC and cmcB. DNA sequencing of the three paralog genes encoding the C. violaceum AmpD amidases revealed mutations of different types in AmpD1 (CV_0566) in most of the spontaneous mutants, but no mutation was found in AmpD2 or AmpD3. Analysis of single and combined null amidase mutants revealed overexpression of both β-lactamases and increased resistance to β-lactams only in mutants with deleted ampD1. When introduced into ampD1 null or spontaneous mutants, the ampD1 gene rescued the antibiotic-related phenotypes. The AmpD1 amidase from C. violaceum has a unique architecture with an N-terminal acetyltransferase domain. Our work offers new insights into the mechanisms of β-lactamase-mediated antibiotic resistance and opens perspectives to improve the treatment of C. violaceum infections.IMPORTANCEResistance to β-lactam antibiotics reduces the options for treating bacterial infections, posing a threat to public health. In this work, we demonstrated that the intrinsic resistance to β-lactam antibiotics in the environmental pathogen Chromobacterium violaceum is mediated by two chromosomally encoded β-lactamases, AmpC and CmcB, and revealed the mechanism that contributes to their simultaneous expression. Our data indicate that mutations in the peptidoglycan recycling amidase ampD1, but not in its paralogs ampD2 and ampD3, lead to stable overexpression of both β-lactamases and increased resistance to β-lactam antibiotics. Remarkably, AmpD1 possesses a unique N-terminal acetyltransferase domain, suggesting a distinct functional mechanism for this enzyme. Our work offers an explanation for the limited effectiveness of many β-lactams in treating C. violaceum infections. Understanding the mechanism of antimicrobial resistance is crucial for developing effective treatments and mitigating the spread of β-lactam-resistant bacteria.